2021
DOI: 10.3389/fonc.2021.763519
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cancer-Associated Fibroblasts in Hepatocellular Carcinoma and the Value of Traditional Chinese Medicine Treatment

Abstract: Invasion and metastasis are the main reasons for the high mortality of liver cancer, which involve the interaction of tumor stromal cells and malignant cells. Cancer-associated fibroblasts (CAFs) are one of the major constituents of tumor stromal cells affecting tumor growth, invasion, and metastasis. The heterogeneous properties and sources of CAFs make both tumor-supporting and tumor-suppression effects possible. The mechanisms for CAFs in supporting hepatocellular carcinoma (HCC) progression can be categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 162 publications
0
16
0
Order By: Relevance
“…Traditional Chinese medicine exhibits various unique properties like varied active substances, multiple key targets, and low toxicity [39]. More importantly, it has superior antitumor properties and can be used to treat different tumors, such as esophageal cancer, liver cancer, pancreatic cancer, and breast cancer [40][41][42][43]. The present study identified the key active ingredients and possible detailed molecular mechanisms of Dahuang against hepatoma through network pharmacology, molecular docking, and survival analysis.…”
Section: Discussionmentioning
confidence: 93%
“…Traditional Chinese medicine exhibits various unique properties like varied active substances, multiple key targets, and low toxicity [39]. More importantly, it has superior antitumor properties and can be used to treat different tumors, such as esophageal cancer, liver cancer, pancreatic cancer, and breast cancer [40][41][42][43]. The present study identified the key active ingredients and possible detailed molecular mechanisms of Dahuang against hepatoma through network pharmacology, molecular docking, and survival analysis.…”
Section: Discussionmentioning
confidence: 93%
“…Apart from the infiltrating immune cells, as the main component of tumor stroma, CAFs participated in the formation of TIME and were involved in the tumor progression and prognosis in HCC (Jia et al, 2021). RAB42 expression was found to be significantly correlated with CAFs in HCC.…”
Section: Discussionmentioning
confidence: 94%
“…Cancer-associated fibroblasts (CAFs) constitute the majority components of stroma in tumor and play multiple roles in facilitating tumor cells proliferation, migration, stemness and supporting the formation of TIME in HCC (Jia et al, 2021). We, therefore, investigated the possible association between the infiltration level of CAFs and the RAB42 expression in HCC.…”
Section: Correlation Between Rab42 Expression and Cancer-associated F...mentioning
confidence: 99%
“…TCM has been proved to reduce the toxicity of chemotherapy drugs, enhance the sensitivity of radiotherapy, minimize the side effects of radiotherapy, and improve the immunity of patients in the treatment of lung cancer [ 22 ]. Moreover, it may also have a potential role in anti-recurrence and metastasis [ 23 ]. TCM against lung cancer can stabilize lesion conditions, prolong the survival period of patients, and benefit patients with better quality of life.…”
Section: Discussionmentioning
confidence: 99%